2014
DOI: 10.4236/ojpm.2014.46050
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Intake of Fruits and Vegetables in Relation to Urinary Estrogen DNA Adduct Ratio

Abstract: Background Estrogen exposure plays a role in breast cancer (BC) development. A novel estrogen biomarker, the estrogen DNA adduct (EDA) ratio, was shown to be elevated in women at high-risk of BC and among BC cases. Modifiable factors may impact the EDA ratio, with studies demonstrating that resveratrol reduces EDA ratio in vitro. We sought to examine the hypothesis that dietary intake of fruits and vegetables is inversely associated with EDA ratio. Methods This analysis was conducted in 53 pre-menopausal, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These properties can potentially influence cancer progression and development through inhibition of metastasis, induction of apoptosis, anti-proliferative activity and inhibition of protein kinase activity ( 70 ) . Soya has been hypothesised to reduce BC risk by shifting oestrogen metabolites that are genotoxic towards other inactive forms ( 63 , 66 ) . Soya is also known to have anti-proliferative, pro-apoptotic, antiangiogenic, antioxidative and anti-inflammatory effects ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties can potentially influence cancer progression and development through inhibition of metastasis, induction of apoptosis, anti-proliferative activity and inhibition of protein kinase activity ( 70 ) . Soya has been hypothesised to reduce BC risk by shifting oestrogen metabolites that are genotoxic towards other inactive forms ( 63 , 66 ) . Soya is also known to have anti-proliferative, pro-apoptotic, antiangiogenic, antioxidative and anti-inflammatory effects ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis suggested a 4-6 % lower risk for each additional recommendation that was met. Several possibly protective mechanisms against cancer can be identified that are associated with the higher consumption of fruit, vegetables (47,(62)(63)(64)(65) and soya (13,66) and a lower BMI, characteristics typical of most vegans in this population. Higher intakes of non-essential amino acids, characteristic of vegan diets, regulate the insulin-glucagon axis (67)(68)(69) , and there are metabolic effects that include greater tissue sensitivity to insulin, and also decreased hepatic production and serum levels of insulin-like growth factor-1.…”
Section: Key Findingsmentioning
confidence: 99%
“… 2 Breast cancer risk is also influenced by estrogen metabolism, and the genotoxic estrogen quinones formed in this process 3 5 can be modulated by dietary means, including botanical dietary supplements (BDSs). 2 , 6 , 7 As traditional hormone therapy (HT) is associated with an increased risk of breast cancer, many women use BDSs, which are perceived as safer alternatives for the relief of menopausal symptoms. 2 , 8 10 However, efficacy claims are not only disallowed for BDSs but also remain questionable for botanicals used in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Although the connection between obesity and breast cancer has been well documented in various studies 10 , the molecular mechanisms fundamental for this correlation are not fully clear. Leptin, an obesity related molecule, is a key player in the progression of several types of cancer including breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, research on compounds that affect the estrogen metabolic pathway is ongoing. Example of these compounds are the dietary supplements resveratrol and N-acetylcysteine 8 and the tumor necrosis factor-alpha (TNF-α) 9 , as well as vegetable and carbohydrate consumption 10 . …”
Section: Introductionmentioning
confidence: 99%